Os sentidos da unidade teoria e prática constituídos no estágio supervisionado em educação infantil - Batista, Luciene (2022)
The present investigation is part of the line of research Teacher Training and Professionalization and Educational Work. It proposes as a theme the unit theory and practice in supervised internship in Early Childhood Education. The guiding axis of the investigation presents the following problem: what meanings do students of the Pedagogy course attribute to the theory and practice unit in the perspective of supervised internship in Early Childhood Education? The general objective was to apprehend and analyze the meanings of the theory and practice unit constituted, in the supervised internship in Early Childhood Education, by students of the Pedagogy course at the Faculty of Education of the Federal University of Goiás. The specific objectives include: Discussing the relationships and contradictions between the supervised internship in EI and the theory and practice unit in teacher training; identify how the supervised internship constitutes a privileged space and time for teacher training for Early Childhood Education; apprehend and analyze how Pedagogy students at the Faculty of Education at the Federal University of Goiás (UFG) understand the theory and practice unit from their experiences in the supervised internship; understand the meanings of the theory and practice unit constituted in the experiences of the supervised internship in early childhood education, elaborated by the students. The research participants were students who were undergoing the internship or had already completed the supervised internship in Early Childhood Education of the Pedagogy Course at the Faculty of Education of the Federal University of Goiás. We base the research theoretically and methodologically on historical-dialectical materialism, since the epistemology of praxis is the category of analysis of teacher training, investigated in this thesis in its concrete totality, one of the fundamental principles of the research's theoretical-methodological framework. We understand that concrete reality is constituted by complex social phenomena that are configured as antagonistic and contradictory and such phenomena are located in a certain historical time, therefore they have a transitory character, that is, they are not inert, they have a movement that generates transformations. We adopted as the main theoretical contributions of the research authors such as Antunes (2004; 2015), Curado Silva (2008; 2019), Dourado (2015; 2016; 2019), Gatti (2010; 2019), Harvey (1992); Kuenzer (2010), Lukács (1079), Marx (2011; 2017; 2001; 2004; 1978; 1984; 1980), Marx; Engels (2001), Mészáros (2011), Pimenta (2020); Saviani (1984; 2013), Shiroma (2003; 2017); Vazquez (2011). For the analysis of research data, we started from the theoretical-methodological categories meanings and senses, and based the discussion on Vygotsky (1996; 2009); Leontiev (2004); Aguiar (2006); Aguiar; Ozella (2006; 2013); Aguiar; Soares; Machado (2015); Aguiar; Machado (2016). Based on the adopted methodology, five core meanings were elaborated, constituted as explanatory categories of the meanings and senses of the theory and practice unit established in the supervised internship in Early Childhood Education, namely: 1) Ambiguities and contradictions in the identification with the Pedagogy course; 2) Meanings of teaching – contradictions between theory and practice; 3) Learning through practice: the contradictory movement of the teacher training process; 4) Meetings and Disagreements between the Institution of Early Childhood Education (EI) and the University in the supervised internship; 5) Relationships and Contradictions of the meanings of the theory and practice unit in the supervised internship. The contradictions observed in relation to the meanings and meanings indicated two fundamental categories for their understanding: pragmatism and praxis. The analysis of the frequency of these categories allowed us to infer that they are mediated, concomitantly, by pragmatic processes, by the emphasis given to practice in the formative process, an aspect that is strongly disseminated and present in current hegemonic policies and at the same time by praxis, due to the awareness regarding the importance of theory to support practice. In this investigation, we defend the importance of praxis and work as an educational and formative principle in the entire formation of professionals in Early Childhood Education and in the particularity of the supervised internship at this level of education, as we understand that theory and practice need to be understood dialectically as inseparable dimensions, although they are different. From this perspective, we understand that, in order to promote teacher training and bring about changes in pedagogical practices, it is fundamental to support theory, in order to achieve a transformed and transforming praxis.